The Role of a Solid Personality in Alleviating Occupational Bullying an Analytical Study of the Perspectives of a Purposive Sample of Teachers at the University of Karbala, College of Administration and Economics - Al-Hasnawi, Saleh Mahdi Mohammed (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
This research aimed to investigate the relationship between the independent variable, Solid Personality, with its dimensions (control, challenge, commitment), and the dependent variable, job bullying, with its dimensions (belittling, undermining work, verbal abuse). The core research question was: "What is the relationship between Solid Personality and job bullying among a purposive sample at the College of Management and Economics, University of Karbala?" The significance of this research was underscored by the insights obtained from a thorough survey and analysis of the opinions of the research sample, which comprised 185 teaching respondents. This sample included the dean, 2 teaching assistants, and 182 teaching staff members. To collect data, a structured questionnaire was developed, based on a five-point Likert scale. The study utilized both descriptive and analytical statistical methods. Descriptive methods included calculating the arithmetic mean and standard deviation, while analytical methods involved linear regression and correlation coefficients, employing the SPSS software. The most critical conclusions drawn from the study highlighted the significant impact of Solid Personality on job bullying within the organization under investigation. The findings revealed that certain personality traits could potentially reduce instances of job bullying, thereby contributing to a more positive and supportive work environment.